2018
DOI: 10.1016/j.pedneo.2017.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Role of Th22 and IL-22 in pathogenesis of allergic airway diseases: Pro-inflammatory or anti-inflammatory effect?

Abstract: A new population of T cells known as Th22 was described for the first time in 2009. These cells are usually identified by the production of IL-22. However, this cytokine is also secreted by other cells such as Th1, Th2, Th17, natural killers, and innate lymphoid cells. Th22 is known as a pro-inflammatory agent in allergic skin diseases. Recently, more evidence has emerged showing associations between these cells and other diseases. The role of Th22 in asthma and allergic rhinitis is controversial: some authors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…However, the role of IL-22 in the allergic airway diseases is still controversial (pro-inflammatory effects vs. anti-inflammatory properties). 28 In this study, we showed that, in patients with CRSwNP, IL-22 expression was positively correlated with type 2 inflammatory cytokines. In addition to eosinophils, mast cells might be the potential source of IL-22 in NP tissues responding to subsequent IgE-mediated signals.…”
Section: Discussionmentioning
confidence: 60%
“…However, the role of IL-22 in the allergic airway diseases is still controversial (pro-inflammatory effects vs. anti-inflammatory properties). 28 In this study, we showed that, in patients with CRSwNP, IL-22 expression was positively correlated with type 2 inflammatory cytokines. In addition to eosinophils, mast cells might be the potential source of IL-22 in NP tissues responding to subsequent IgE-mediated signals.…”
Section: Discussionmentioning
confidence: 60%
“…It has been recognized that the interleukin (IL) family members are involved in the etiologies of various inflammation-related conditions, such as infectious diseases [4][5][6], immunological disorders [7][8][9][10] and neoplasms [10]. In a comprehensive review article that depicted IL-6 profiles in patients receiving different cardiac operations.…”
Section: Introductionmentioning
confidence: 99%
“…Our ndings support hypothesis of antiin ammatory effect of IL-22 in persistent allergic airway diseases. However, experimental, and clinical studies provide controversial data about possible role of IL-22 in these diseases (14,21).…”
Section: Discussionmentioning
confidence: 99%
“…It is thought that type 1 and type 3 immunity is important in the development of autoimmune disorders or chronic non-allergic airway in ammation (11,12). However, there are evidences that IL-22 can also be involved in allergic airway in ammation (13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation